If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f(x) = 1 + x Multiply f * x fx = 1 + x Solving fx = 1 + x Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Divide each side by 'x'. f = x-1 + 1 Simplifying f = x-1 + 1 Reorder the terms: f = 1 + x-1
| 5x+30+x=144 | | 3(s-5)=45 | | s-5=21 | | 14x+20=16x | | x+30=560 | | (-3a^2b^4)^2/3(a^2b)^3 | | d(t)=35 | | 3s-5=45 | | (x)=2x+9 | | 48+56+3x+11x=x | | 5x+5y=x+2y | | 10x-31=59 | | .3x-3x+1.6=.6 | | 30+x=560 | | -1/3x-7=-3 | | 3x-(5x-3)=-1 | | 4(x+2x)=16 | | -5(8m+3-3m+3)= | | 5x-19=91 | | r-(-2)=7.26 | | 2(4x-1)=42 | | d(t)=50t | | 15ax-2y+3ay-10x= | | -6(-4+6x)=24 | | 2x-100=62 | | 5x+8-3(x+1)=7x+8 | | 7n-8=2 | | 10c=12 | | -3-(8)+(-2)=x | | 30x^2+7d-15=0 | | -3-(8)+(-2)= | | -3s^2+28s-48=0 |